Pigmentation and Genotype Effects, Phenotypic Stability for Anthocyanins, Phenolic Compounds and Antioxidant Activity in the Corn Tassel - Prakasit Duangpapeng; Khundej Suriharn; Kamol Lertrat; Khomsorn Lomthaisong; Marvin Paul Scott (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
The tassels of corn can be utilized as a co-product for the production of phytochemicals. The objectives were to assess the impact of pigmentation and genotype on the levels of anthocyanins, phenolic compounds and antioxidant activity, and to determine the phenotypic stability of these traits. Sixteen genotypes were evaluated at two locations over two seasons. Corn genotypes in purple or pink pigmentation group had higher anthocyanin concentration and DPPH radical scavenging activity in tassel than those in normal green group. Tassel color can be used as a selection criterion to improve anthocyanin and antioxidant activity, but the trait is not effective to predict the phenolic concentration in the tassel. Genotype is an important source of variation for all parameters. The sensitivity of corn genotypes with high levels of measured compounds to the environment indicates the importance of choosing suitable locations and seasons for the production of high-quality corn tassels as a co-product of grain and vegetable corn. The findings of this study can be valuable for producers who intend to select genotypes for phytochemical production in corn tassels, as well as to corn breeders who aim to develop improved varieties with high yield and high bioactive phytochemicals in tassel.